Forest planning, rural practices, and woodland cover in an 18th-century Alpine Valley (Val di Fiemme, Italy): A geohistorical and GIS-based approach to the history of environmental resources - Nicola Gabellieri; Ettore Sarzotti (AIMS Geosciences)
The importance of past human activities in determining the extent and composition of current woodland cover has long been recognized. Understanding the environmental dynamics that have characterized vegetation over time, as well as the productive rural practices associated with them, can have significant repercussion on the current and future management of environmental resources. Scholars have identified a significant shift in woodland exploitation regimes in Europe, occurring between the late 18th and early 19th centuries. During this period, several states introduce modern forestry which gradually replaced local agro-silvo-pastoral structures. Geohistorical sources can help reconstruct these previous management systems and provide information on past environments. This paper has two main objectives: to increase knowledge of environmental and landscape dynamics in the Alpine context through a specific case study, and demonstrate the potential of geographic information systems (GIS) software in handling geohistorical sources. The case study of Val di Fiemme (Italy) has been chosen for two reasons: it is an area that has high forest presence and peculiar vegetation cover and the local archive contains a great deal of documentation. Specifically, the documents drafted by an Austrian Commission for forest management in the 18th century have been interpreted as an attempt by the Habsburg Crown to restructure the valley towards a timber economy. Documentation was collected, digitized, and mapped to build a historical GIS, showing woodland ownership status, tree species, and practices in the 18th century. As a result, a socio-ecological system was identified that significantly differs from the current one, revealing a greater diversity of species. The establishment of Habsburg norms represents a watershed in forest management with direct environmental effects that can be seen over the subsequent century. In conclusion, the study demonstrates the potential of using GIS-based approaches to analyze textual geohistorical sources and extend the analyzed diachrony to periods prior to the geometrical cartographic ones.